2019
DOI: 10.1021/acs.jpcc.9b00600
|View full text |Cite
|
Sign up to set email alerts
|

Toward High Activity and Durability: An Oxygen-Rich Boron Nitride-Supported Au Nanoparticles for 4-Nitrophenol Hydrogenation

Abstract: Catalytic hydrogenation of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) is widely recognized as one of the most effective solutions to deal with the water-related environmental issues, where catalysts with high activity and long cycle life are always pursued. In this paper, oxygen-rich boron nitride (BNO)-supported Au nanoparticles (Au/BNO) were proposed to serve as catalysts for 4-NP hydrogenation. Our results show that the Au nanoparticles are well dispersed on the highly porous BNO substrate with a small pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…(a) Peak catalytic efficiency (e.g., TOF) toward 4-NP hydrogenation of the present catalyst in this work and other recently reported noble-metal NP-based catalysts reported within the recent 3 years. Data adapted from references. ,, The inset in (a) is a plot of ln­( A / A 0 ) of 4-NP against time for the catalyst. Plots of ln­( A / A 0 ) against time of (b) CR hydrogenation and (c) MO hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…(a) Peak catalytic efficiency (e.g., TOF) toward 4-NP hydrogenation of the present catalyst in this work and other recently reported noble-metal NP-based catalysts reported within the recent 3 years. Data adapted from references. ,, The inset in (a) is a plot of ln­( A / A 0 ) of 4-NP against time for the catalyst. Plots of ln­( A / A 0 ) against time of (b) CR hydrogenation and (c) MO hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, ultrathin BN NSs exhibited high affinity toward the adsorption of glycerol molecules via electrostatic interactions and, thus, adsorbed glycerol molecules were converted into LA and other byproducts, over the catalytic sites of ultrathin BN NSs under base conditions. 34 Meanwhile, Au/BN catalysts showed an enhanced conversion efficiency of glycerol (75%), yield (55%), and higher LA selectivity (74%) than pure BN NSs, due to higher catalytic activity of Au NPs. Similar catalytic performance was observed over the surfaces of HAp/BN catalysts, though they produced higher LA yield (60%), LA selectivity (75%), with higher glycerol conversion efficiency (80%), along with noticeable formation of pyruvaldehyde selectivity (12%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…33−36 Recent studies have shown that BN nanohybrids, dispersed by Au NPs, show higher catalytic activity toward hydrogenation and reduction of 4-nitrophenol (4-NP) in 2.5 min, with a high conversion rate constant of 2.25 min −1 . 34 Thus, the potential for the individual catalytic activity of Au NPs, HAp, and BN NSs presents a good scope to study their synergistic catalytic performance through the synthesis of the Au/HAp/BN ternary nanocomposite and its application for glycerol conversion to LA. Previous studies used polydopamine as a "glue layer", which acted as a binding layer between Au NPs and BN NSs surfaces to prevent the agglomeration of individual NPs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous catalysts based on metal nanoparticles (NPs) are promising tools for wastewater treatment. Typically, metal NPs are loaded onto a support such as carbon nanotube, 1 graphene, 2 boron nitride, 3 clay, 4 metal oxides, 5 or polymers 6 to prevent aggregation. Thus, improving the dispersion stability of metal NPs on a support is critical for the design and synthesis of high-performance heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%